Recent applications of Kampo treatment for neurological diseases. Issue 1 (4th January 2023) - Muramatsu, Shin‐ichi; Tamada, Mayumi; Harada, Yoshinao; Raimura, Masaki; Kwon, Seungwon
Abstract: Background: Although various new drugs have been developed for neurological diseases, many diseases have no effective treatment or only inadequate efficacy. Here we introduce some examples of effective Kampo treatment. Key Findings: (1) Parasomnia in the elderly is preceded by the onset of diffuse Lewy body disease, with symptoms such as nightmares and loud screaming in the middle of the night. Keishikaryukotsuboreito (KSTRB), indicated in the classics for treating parasomnia, was effective in alleviating the symptoms. KSTRB is also used for enuresis that persists into adulthood. (2) Chronic subdural hematomas (CSDHs), treated by hematoma removal with burr‐hole surgery, recur at a rate of up to 20%. Goreisan (GRS) reduces hematoma volume and prevents postoperative CSDH recurrence. Homogeneous CSDH was most responsive to GRS in preventing recurrence. (3) Migraine frequently interferes with daily life. Keishibukuryogan (KBG), which alleviates blood stasis, was effective for patients with both menstruation‐associated migraine and scintillating scotomas. (4) Many traditional herbal medicines are listed in the Korean Medicine Clinical Practice Guideline for Stroke in Korea. Chunghyuldan, a related formula of Orengedokuto (OGT), is mainly used to prevent stroke. Conclusion: Kampo medicine is being applied in new and effective ways to treat various neurological diseases. Hopefully, more clinicians will recognize the usefulness of such Kampo medicines and utilize them in their daily practice.